Peningkatan Kuat bentur Produk 3D Printing Fused Deposition Modeling menggunakan Filamen Polypropylene - Wulandari, Sawitri; Pristiansyah, Pristiansyah; Husman, Husman (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
In the world of manufacturing technology there is the latest breakthrough called 3D Printing which is based on layer manufacturing. In making products, a method of adding material in layers is used, usually called additive manufacturing. The principle used in this manufacturing process technology is layered modeling, by converting 3D data directly from computer-aided design (CAD) into a physical model. Many manufacturing technologies have been developed to make prototypes according to needs, for example FDM (Fused Deposition Modeling). Setting factors and experimental levels is an important step in maximizing the quality of research level products referring to transparent materials formed from polypropylene filaments. The factors that vary are Nozzle Temperature, Bed Temperature, Print Speed, and Layer Height. This research design uses the Taguchi method. This research uses an L9 orthogonal matrix with 3 levels. Based on the results of the research carried out, we can conclude that in the impact strength test there is an increase in the results of the impact strength test with the most influential process parameters, respectively, namely Print Speed (35mm/s), Layer Height (0.3mm), Bed Temperature (97 °C) and Nozzle Temperature (215°C) using Polypropylene filament. So the strongest impact strength test value is in experiment no. 2 with an average value of 0.03370 Joules and the weakest is in experiment no. 1 with an average value of 0.02959 Joules.